PENGARUH MODAL SOSIAL TERHADAP ADOPSI BUDIDAYA KEDELAI HITAM MALLIKA OLEH ANGGOTA KELOMPOK TANI MITRA PT UNILEVER DI KABUPATEN BANTUL - , DEVI NIRMALAWATI, Ir. Roso Witjaksono, M.S. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
This research aims to find out: (1) the level of social capital in the adoption of farmers cultivating Mallika black soybean, (2) the factors that influence social capital, and (3) the influence of social capital on the adoption of black soybean cultivation Mallika. The research was conducted in sub-district Imogiri, Bambanglipuro, and Pundong, Bantul regency with farmers studied were black soybean farmers associate with PT Unilever. The basic method used in this research is descriptive analytical method with survey technique. Villages sampling have been selected purposively, in Sriharjo, Sumbermulyo, and Srihardono. From each village was selected purposively 1 farmer group, and further from each sample group was chosen 12 samples taken randomly, so the overall sample obtained 60 farmers. To test the hypothesis used the proportion test, multiple linear regression analysis, and simple linear regression analysis. The results showed that social capital is still relatively moderate with a percentage of 76.67%. The factors that significantly affect the role of social capital are the village officials, the role of leaders of farmer groups and farmer attitudes towards partnership. Factors that did not significantly affect farmers' social capital: the are role of workers PT Unilever, land area, the role of traders, and active farmers in farmer groups. Black soybean adoption by members of the black soybean farmer groups is categorized relatively high at percentage of 75.94%. Social capital of black soybean farmer group members Mallika positively affected on the adoption of black soybean cultivation.